2019
DOI: 10.3310/hsdr07180
|View full text |Cite
|
Sign up to set email alerts
|

Births and their outcomes by time, day and year: a retrospective birth cohort data linkage study

Abstract: BackgroundStudies of daily variations in the numbers of births in England and Wales since the 1970s have found a pronounced weekly cycle, with numbers of daily births being highest from Tuesdays to Fridays and lowest at weekends and on public holidays. Mortality appeared to be higher at weekends. As time of birth was not included in national data systems until 2005, there have been no previous analyses by time of day.ObjectivesTo link data from birth registration and birth notification to data about care durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 83 publications
(135 reference statements)
1
46
0
Order By: Relevance
“…These tend to have more complex data, although similar algorithms were successfully used for the quality of assurance of the linkage of multiple births to mothers’ delivery records. 6 In addition, the algorithms used in this study were deterministic, rather than probabilistic. The latter can be more effective when dealing with complex records, such as those with a lot of missing data or coding errors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These tend to have more complex data, although similar algorithms were successfully used for the quality of assurance of the linkage of multiple births to mothers’ delivery records. 6 In addition, the algorithms used in this study were deterministic, rather than probabilistic. The latter can be more effective when dealing with complex records, such as those with a lot of missing data or coding errors.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we did not assess whether the quality of linkage for multiples is comparable with live, singleton, NHS hospital births although QA of the linkage of multiple births to mothers’ delivery records suggested that it was better than had been initially assumed. 6 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations